The role of miRNAs in the development of Super-Tregs as a potential therapy for neurodegenerative diseases - Mukherjee, Kamalika; Bhattacharyya, Suvendra N. (Frontiers in Immunology, 2026)
Regulatory T cells, or Tregs, are designed to limit unnecessary inflammation and serve as a safeguard mechanism to prevent tissue damage caused by heightened inflammatory responses from activated macrophages or effector T cells. Impaired Treg function has implications in autoimmunity and neuroinflammation. Neuroinflammation triggered by amyloid proteins and protein aggregates accelerates neurodegeneration due to increased cytokines and chemokines in the brains of individuals with Alzheimer’s Disease and Parkinson’s Disease. A simple approach involves preventing inflammation by suppressing T-effector cell activity in affected brains through boosting Tregs’ function. Super-Tregs, with enhanced anti-inflammatory properties, can be engineered in vitro to combat inflammation in various tissues and, after homotropic transfer to the target tissue, prevent damage caused by inflammation. The development of Super-Tregs can be achieved through specific genetic and epigenetic modifications. Efforts to generate Super-Tregs utilizing miRNAs and miRNA-containing extracellular vesicles hold promise in treating neuroinflammation with miRNA-engineered Super-Tregs. In this review, we discuss the potential, progress, challenges, and limitations of Super-Treg development and their application in the treatment of neurodegeneration.